Dynamic tracing of sugar metabolism reveals the mechanisms of action of synthetic sugar analogs. (25th October 2021) - van Scherpenzeel, Monique; Conte, Federica; Büll, Christian; Ashikov, Angel; Hermans, Esther; Willems, Anke; van Tol, Walinka; Kragt, Else; Noga, Marek; Moret, Ed E; Heise, Torben; Langereis, Jeroen D; et al.
Abstract: Synthetic sugar analogs are widely applied in metabolic oligosaccharide engineering (MOE) and as novel drugs to interfere with glycoconjugate biosynthesis. However, mechanistic insights on their exact cellular metabolism over time are mostly lacking. We combined ion-pair ultrahigh performance liquid chromatography–triple quadrupole mass spectrometry mass spectrometry using tributyl- and triethylamine buffers for sensitive analysis of sugar metabolites in cells and organisms and identified low abundant nucleotide sugars, such as UDP-arabinose in human cell lines and CMP-sialic acid (CMP-NeuNAc) in Drosophila. Furthermore, MOE revealed that propargyloxycarbonyl (Poc)-labeled ManNPoc was metabolized to both CMP-NeuNPoc and UDP-GlcNPoc. Finally, time-course analysis of the effect of antitumor compound 3Fax -NeuNAc by incubation of B16-F10 melanoma cells with N -acetyl-D-[UL- 13 C6]glucosamine revealed full depletion of endogenous ManNAc 6-phosphate and CMP-NeuNAc within 24 h. Thus, dynamic tracing of sugar metabolic pathways provides a general approach to reveal time-dependent insights into the metabolism of synthetic sugars, which is important for the rational design of analogs with optimized effects.